Forest productivity in southwestern Europe is controlled by coupled North Atlantic and Atlantic Multidecadal Oscillations - Jaime Madrigal-González (Nature Portfolio, 2017)
The North Atlantic Oscillation (NAO) drives biological responses in terrestrial ecosystems through oscillatory modes of climatic variability. Here, the authors show how landscape scale productivity responses to NAO are contingent upon the Atlantic Multidecadal Oscillation in southwestern Europe.